Different effects of I-wave periodicity repetitive TMS on motor cortex interhemispheric interaction - Tian, Dongting; Izumi, Shin-Ichi (Frontiers in Neuroscience, 2023)
Background Activity of the neural circuits in the human motor cortex can be probed using transcranial magnetic stimulation (TMS). Changing TMS-induced current direction recruits different cortical neural circuits. I-wave periodicity repetitive TMS (iTMS) substantially modulates motor cortex excitability through neural plasticity, yet its effect on interhemispheric interaction remains unclear. Objective To explore the modulation of interhemispheric interaction by iTMS applied in different current directions. Materials and Methods Twenty right-handed healthy young volunteers (aged 27.5 ± 5.0 years) participated in this study with three visits. On each visit, iTMS in posterior–anterior/anterior–posterior direction (PA-/AP-iTMS) or sham-iTMS was applied to the right hemisphere, with corticospinal excitability and intracortical facilitation of the non-stimulated left hemisphere evaluated at four timepoints. Ipsilateral silent period was also measured at each timepoint probing interhemispheric inhibition (IHI). Results PA- and AP-iTMS potentiated cortical excitability concurrently in the stimulated right hemisphere. Corticospinal excitability of the non-stimulated left hemisphere increased 10 min after both PA- and AP-iTMS intervention, with a decrease in short-interval intracortical facilitation (SICF) observed in AP-iTMS only. Immediately after the intervention, PA-iTMS tilted the IHI balance toward inhibiting the non-stimulated hemisphere, while AP-iTMS shifted the balance toward the opposite direction. Conclusions Our findings provide systematic evidence on the plastic modulation of interhemispheric interaction by PA- and AP-iTMS. We show that iTMS induces an interhemispheric facilitatory effect, and that PA- and AP-iTMS differs in modulating interhemispheric inhibition.